[Early on-campus dining hall] (1910)
Men and women congregated indoors at wooden chairs and tables for a meal together. Room appears to have a dirt floor. Shelving unit located in rear of room and is being used to store personal belongings. Back of photograph reads "Okay everybody altogether now, Mic-key Mo-us-e"